EFEKTIFITAS AKAR SORGUM SEBAGAI BIOHERBISIDA TERHADAP Testplant SECARA In Vitro - Utami, Rizky Septika (Jurnal Agroteknologi dan Pertanian (JURAGAN), 2022)
Weeds as competitors for nutrients, water, sunlight and growing space for staple crops. The experiment was the evaluation of the effectiveness of sorghum root bioherbicides on the in vitro plant test using a Completely Randomized Design (CRD) with two factors namely the concentration of bioherbicide and the type of plant test. The first factor consists of 5 levels, 0%, 2.5%, 5%, 7.5%, and 10%. The second factor consists of 2 (two) test plants, namely green beans (representing broadleaf weeds) and rice (representing narrowleaf weeds). The results showed that the higher the concentration of sorghum root bioherbicides, the percentage of normal sprouts, the length of the radicles and the length of the plumula.